Waqf Development Model for SDG-16 (Peace, Justice and Strong Institutions) - Rusydiana, Aam Slamet; Sukmana, Raditya; Laila, Nisful (Islamic Social Finance, 2023)
Waqf-based development is in line with the goals of the SDGs. Waqf institutions play an important role in actualizing the SDGs targets including point 16 which is peace, justice and strong institutions. This study aims to design and propose a waqf model for SDGs point 16 peace, justice, and strong institutions in the world by combining the concept of waqf with the activities of related institutions. This research proposes that the best waqf-SDGs model for point 16 is the integrated Waqf & ZIS model. This model is a type of waqf that is social in nature, where waqf is collaborated with ZIS instruments. So that the utilization of this instrument is suitable for social purposes. The implementation of the waqf models that have been proposed with their respective priorities can potentially become an Islamic social fund instrument that participates in supporting the SDGs to ensure that all humans can enjoy a prosperous life and advance economically, socially, and technologically in harmony with nature.